Effect of wing flexibility on aircraft flight dynamics - Qiao, Yuqing (Cranfield University, 2012)
The purpose of this thesis is to give a preliminary investigation into the effect of wing deformation on flight dynamics. The candidate vehicle is FW-11 which is a flying wing configuration aircraft with high altitude and long endurance characteristics. The aeroelastic effect may be significant for this type of configuration. Two cases, the effect of flexible wing on lift distribution and on roll effectiveness during the cruise condition with different inertial parameters are investigated. For the first case, as the wing bending and twisting depend on the interaction between the wing structural deflections and the aerodynamic loads, the equilibrium condition should be calculated. In order to get that condition, mass, structure characteristics and aerodynamic characteristics are estimated first. Then load model and aerodynamic model are built. Next the interaction calculation program is applied and the equilibrium condition of the aircraft is calculated. After that, effect of wing flexibility on lift parameters is investigated. The influence of CG, location of lift and location of flexural axis are investigated. The other case is to calculate the transient roll rate response and estimate the rolling effectiveness of flexible aircraft, and compared with the rigid aircraft’s. A pure roll model is built and derivatives both for the rigid wing and the flexible wing are estimated. It has been found that flexible wing leads to the loss of control effectiveness, even cause reversal when reduces the structure natural frequency. The influence of inertia data for flexible roll is also investigated.
Keywords: Static aeroelasticity; wing deformation; lift distribution; roll effectiveness